2009
DOI: 10.1016/j.ijsu.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of controlled-intermittent anal dilatation and lateral internal sphincterotomy in the treatment of chronic anal fissures: A prospective, randomized study

Abstract: CIAD applied with a standardized technique reduced anal canal resting pressure and provided symptomatic healing that was equivalent to a LIS. Since there were no findings of incontinence, or situations which resulted in sphincter damage, we conclude that CIAD is suitable for patients with chronic anal fissures because it is less invasive than LIS, with equivalent efficacy and safety. In addition, the CIAD method may be an alternative procedure in older and multiparous women who has a higher risk of incontinenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…6,7,[9][10][11] Majority that is 70% are observed in 20 to 40 years which is also consistent with the literature. Male to female ratio was practically equal 1.07:1 suggesting the equal distribution of gender in patients suffering from chronic fissure in ano.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…6,7,[9][10][11] Majority that is 70% are observed in 20 to 40 years which is also consistent with the literature. Male to female ratio was practically equal 1.07:1 suggesting the equal distribution of gender in patients suffering from chronic fissure in ano.…”
Section: Discussionsupporting
confidence: 91%
“…The mean duration of pain was 12 months in the present study, which is quite consistent with the literature and this signifies that the study includes the cases with chronic fissure in ano. 6,[9][10][11] The site of fissure in the majority of patients (83.3%) was at posterior midline (6 o'clock position). Fissure at anterior midline (12 o'clock) was seen in 9.3% patients and fissure at both anterior and posterior midline is seen in 7.4% patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) In the early 1990s, however, being a repeatable method anal dilation proved to be very effective and showed a very low incidence of side effects. Since then at least one controlled, randomised study has shown there to be a little difference in healing rates and complications between controlled anal dilation and lateral internal sphincterotomy, (7) while another has again shown high success rates with anal dilation coupled with low incidence of side effects. (16) The results of anal dilatation using a bivalve anoscope, also called as endoscopic dilatation are comparable with those of lateral sphincterotomy and can be achieved at a lower complication rate with only minor and temporary complications and performed by physicians with no specific surgical training.…”
Section: Discussionmentioning
confidence: 99%
“…Une « sphinctérolyse » correspondant à une rupture des fibres du sphincter interne par un appui ferme d'un doigt intra-canalaire permet 96,5 % de cicatrisation avec 3,5 % d'incontinence anale récupérant dans 97 % des cas [53]. Une dilatation contrôlée avec un dilatateur anal ouvert progressivement jusqu'à 48 mm par intermittence [54] ou avec un ballon pneumatique [55] a été comparée à la sphinctérotomie latérale interne. Les résultats sont encourageants, similaires à la sphinctérotomie en termes de cicatrisation avec une tendance à moins d'incontinence anale.…”
Section: Dilatation Analeunclassified